2020
DOI: 10.32983/2222-4459-2020-2-413-421
|View full text |Cite
|
Sign up to set email alerts
|

Financial Ratios as Indicators for Identification of Financial Risks of Industrial Enterprises

Abstract: Ільчук В. П., Шишкіна О. В. Фінансові показники як індикатори виявлення фінансових ризиків промислових підприємств Метою статті є дослідження можливостей використання показників оцінки фінансового стану промислових підприємств як індикаторів виявлення ймовірності виникнення фінансових ризиків для своєчасного усунення загроз фінансових втрат і банкрутства. У результаті дослідження обґрунтована необхідність використання фінансових показників як індикаторів виявлення фінансових ризиків промислових підприємств, дл… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Most Chinese companies still need to incorporate financial risk management into their daily management, the corporate financial risk is not yet widely managed, which was put forward at the first insurance conference of the American Management Association [ 5 ]. Ilchuk and Shyshkina found that later, with the continuous development and improvement of risk management theory and practice, people began to gradually introduce these theories and practices into enterprise financial risk management [ 6 ]. Boiko and Gevrek found that, managing corporate financial risk, it is necessary to analyze the causes of enterprise financial risks and identify and measure financial risks; that is, the evaluation of enterprise financial risk is the basis; managing corporate financial risks, its purpose is to adopt economically reasonable control strategies and avoid or diversify risk, to avoid losses; that is, the control of enterprise financial risk is the key, as shown in Figures 2 and 3 [ 7 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most Chinese companies still need to incorporate financial risk management into their daily management, the corporate financial risk is not yet widely managed, which was put forward at the first insurance conference of the American Management Association [ 5 ]. Ilchuk and Shyshkina found that later, with the continuous development and improvement of risk management theory and practice, people began to gradually introduce these theories and practices into enterprise financial risk management [ 6 ]. Boiko and Gevrek found that, managing corporate financial risk, it is necessary to analyze the causes of enterprise financial risks and identify and measure financial risks; that is, the evaluation of enterprise financial risk is the basis; managing corporate financial risks, its purpose is to adopt economically reasonable control strategies and avoid or diversify risk, to avoid losses; that is, the control of enterprise financial risk is the key, as shown in Figures 2 and 3 [ 7 ].…”
Section: Literature Reviewmentioning
confidence: 99%